Place of surgery in the management of post‐operative chronic pain after placement of prosthetic material based on a series of 107 cases. Issue 7 (23rd March 2018) - Leonard, Grégoire; Perrouin‐Verbe, Marie‐Aimée; Levesque, Amélie; Riant, Thibault; Normand, Loïc Le; Labat, Jean‐Jacques; Rigaud, Jérôme
Abstract : Aims: The objective of this study was to evaluate the efficacy of surgical removal of prosthetic material, possibly combined with nerve release, on chronic postoperative pain following placement of prosthetic material. Material and methods: Single‐tertiary‐centre study on 107 patients managed between November 2004 and April 2016 for removal of prosthetic material responsible for postoperative chronic pain: retropubic suburethral sling ( n  = 32), transobturator suburethral sling ( n  = 50), prolapse mesh ( n  = 16), and hernia mesh ( n  = 9). The primary endpoint was at least 50% reduction of pain evaluated by a pain numerical rating scale (NRS). Results: The mean interval between the initial operation involving placement of prosthetic material and reoperation for removal of prosthetic material was 41.2 ± 35.4 months. In all cases pain apperaed immediately following prosthetic material placement surgery. Pain presented neuropathic features in almost 30% of cases and was poorly systematized in more than one‐half The mean follow‐up of the study population was 8.4 ± 10.3 months. The mean pain NRS score for the overall population was seven preoperatively and three at last follow‐up. At least 50% reduction of the pain NRS score was observed 67% of cases at last follow‐up. During follow‐up, 45% of patients experienced relapse of the disorder for which the prosthetic material was initially placed with, in particular, a 62% recurrence rate of urinary incontinence after removal of transobturator suburethral tape. Conclusion: Surgical removal of prosthetic material to treat chronic postoperative pain, achieved global improvement of pain in about two‐thirds of cases, but with a risk of recurrence of the initial disorders.